GUARANTEED ADAPTIVE TERMINAL CONTROL OF AN AEROSTATIC AIRCRAFT BASED ON DIFFERENTIAL GAME APPROACH - Ziatdinov, Yuriy; Gusynin, Viacheslav; Gusynin, Andrii (Proceedings of National Aviation University (archive), 2020)
Purpose: The present paper is aimed to the problem solution of game algorithms construction for the injection control of an unmanned aerostatic aircraft into the desired terminal conditions under the influence of unknown turbulences. Methods: The problem is solved on the basis of multistep differential transform method and the theory of differential games. Results: The proposed approach does not require numerical integration of differential equations of aircraft motion, reduces the problem of control algorithms synthesis to the solution of final system of equations concerning control variables and turbulence parameters, allows for analytical transformations and allows to synthesize control algorithms that own the property of adaptation to the turbulence action and provide a guarantee of the aircraft injection into desired terminal conditions. The solution of the synthesis problem of guaranteed adaptive control of the process of multistep injection of an unmanned aerostatic aircraft into the desired terminal conditions in the form of mathematical model of differential game is considered. Discussion: Application of the differential-game approach to the control algorithms synthesis of dynamic objects under the action of undetermined turbulences allows to carry out continuous calculations of program strategies for players in real time and get the opportunity to control dynamic objects with feedback, taking into account the action of different turbulences.